TEKNIK PENGUJIAN BOUNDARY VALUE ANALYSIS PADA APLIKASI LEARNING MANAGEMENT SYSTEM POLINELA - Zuriati Zuriati; Dewi Kania Widyawati; Imas Sukaesih Sitanggang; Agus Buowo (LPPM STMIK Pringsewu, 2018)
This study discusses the testing process of the Lampung State Polytechnic e-learning application called the Polinela Learning Management System (LMS). The testing phase is one of the stages in the development cycle of a software. This stage is a series of activities carried out to find errors or shortcomings of a software or computer application. There are several techniques used to test software including black box testing techniques. In this study using black box testing with a boundary value analysis technique to test e-learning applications that have been applied to the Informatics Management program of the Lampung State Polytechnic. The boundary value analysis technique works by determining the lower and upper limit values of the data to be tested, then the data is inputted into the LMS Polinela application. The stages of research carried out begin by determining the functionality to be tested, designing test scenarios, determining the data to be tested, determining the upper and lower limit values according to the database structure that has been created, conducting testing experiments, documenting the results of research, and drawing conclusions. The test results show that there were no errors in the LMS Polinela application when validating the data to be processed.